Photothermocatalytic conversion of CO2 by LDHs@AC composites - Ruiqi Li; Jie Ling; Dongqiang Lei (Results in Engineering)
The key to photocatalytic conversion of CO2 is to improve the efficiency of solar energy utilization. Numerous studies have been devoted to modulating the forbidden bandwidth of photocatalytic materials, thereby altering the response of catalysts to light irradiation. In this paper, CO2 conversion efficiency enhancement by photothermal catalytic means using precious metal-free LDHs@AC composites. The results show that photothermal catalytic conversion is 3.3 times more efficient than photocatalytic conversion in CO2 conversion. The photocurrent transient response results show that the LDHs@AC material in the photothermal catalytic reaction, at higher experimental temperatures, the transfer of electrons from Ti1Li3Al2-LDHs to move the AC is faster, and the rate of the redox reaction is increased, which significantly improves the photocatalytic performance of the LDHs material.